Organizational Acceptability of Implementing SBIRT for Adolescents in Primary Care. (24th August 2021) - Monico, Laura B.; Mitchell, Shannon Gwin; Gryczynski, Jan; Dusek, Kristi; Oros, Marla; Hosler, Colleen; Brown, Barry S.; Ross, Tyler; Schwartz, Robert P.
Abstract: Introduction: Adolescent illicit drug, tobacco, and alcohol use can result in sudden and long-term negative health consequences. Primary care environments present the optimal opportunity for screening and brief interventions that target prevention and curtailing use. Screening, Brief Intervention, and Referral to Treatment (SBIRT) is a service delivery method that could potentially be well-integrated into primary care settings and used to serve a high volume of adolescents. Methods : This qualitative analysis of clinic staff interviews ( N  = 20), collected during a large cluster-randomized trial to implement two models of adolescent SBIRT, examined barriers and facilitating factors to overall acceptability of SBIRT. This study was conducted in a large, urban Federally Qualified Health Center (FQHC) at 7 sites throughout Baltimore City, Maryland, USA. Participants from each clinic included a range of various roles and responsibilities including: medical assistants ( n  = 3), nurses ( n  = 3), primary care providers ( n  = 4), behavioral health counselors ( n  = 4), and administrators ( n  = 6). Results : Results indicate both barriers and facilitating factors for acceptability of SBIRT in terms of (1) universal screening, (2) provider time demands, (3) behavioral health collaboration, and (4) behavioral health caseloads. Discussion : Universal screening was acceptable to participants across organizational roles, but brief interventions and referrals to treatment were found substantially less acceptable.